2015
DOI: 10.1016/j.cell.2015.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the L Protein of Vesicular Stomatitis Virus from Electron Cryomicroscopy

Abstract: The large (L) proteins of non-segmented, negative-strand RNA viruses, a group that includes Ebola and rabies viruses, catalyze RNA-dependent RNA polymerization with viral ribonucleoprotein as template, a noncanonical sequence of capping and methylation reactions, and polyadenylation of viral messages. We have determined by electron cryomicroscopy the structure of the vesicular stomatitis virus (VSV) L protein. The density map, at a resolution of 3.8 Å, has led to an atomic model for nearly all of the 2109-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
355
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(369 citation statements)
references
References 50 publications
10
355
2
2
Order By: Relevance
“…In contrast, RdRps that initiate RNA synthesis at the NP gene start site and then cap the nascent NP mRNA become committed to transcription (23,24). Structural studies of both sNSV and nsNSV RdRps suggest that both can be found in a number of alternative states or conformations, each of which may be important during different steps of RNA synthesis (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, RdRps that initiate RNA synthesis at the NP gene start site and then cap the nascent NP mRNA become committed to transcription (23,24). Structural studies of both sNSV and nsNSV RdRps suggest that both can be found in a number of alternative states or conformations, each of which may be important during different steps of RNA synthesis (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Neutron diffraction is still a problem (and neutrons have the potential to be enormously useful in understanding the structures of water) because large crystals are required, and because neutrons are scarce. High-resolution electron cryomicroscopy is making astonishing advances in efforts to determine the structures of complex molecules [92,93] , but is extraordinarily expensive and complicated. Any consideration of mechanism, or thermodynamics, ultimately must rest on knowing the structures of the reactants and products.…”
Section: Technical Opportunitiesmentioning
confidence: 99%
“…This Cterminal component of L proteins of NNS RNA viruses, especially the region between domains V and VI, is highly variable, and considered as a domain of L which interacts with unique host cell transacting transcriptional cofactors (Dortmans et al, 2011;Poch et al, 1990;Sidhu et al, 1993). The mutations in guinea pig-lethal MARV L protein, however, affect the domain III close to the GDNQ/E motif, presumably directly modulating the processivity of viral RNA-dependent RNA polymerase (Liang et al, 2015). Hence, changes in the polymerase activity of L mutants are expected to be independent of direct interactions with host factors.…”
mentioning
confidence: 99%
“…1a). The recently published structure of vesicular stomatitis virus polymerase L suggests that mCherry is located close to the methyltransferase domain of the enzyme (Liang et al, 2015). Insertion of mCherry-L in a homologous region did not impair the function of EBOV L protein (Hoenen et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation